2021
DOI: 10.2113/2021/2550879
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Paleoearthquakes and Coseismic Slips on a Normal Fault Using High-Precision Quantitative Morphology: Application to the Jiaocheng Fault in the Shanxi Rift, China

Abstract: The quantitative morphology of bedrock fault surfaces combined with aerial surveys and field identification is a useful approach to identify paleoearthquakes, obtain coseismic slips, and evaluate the seismogenic capacity of active faults in bedrock areas where traditional trenching methods are not applicable. Here, we report a case study of the Jiaocheng Fault (JCF) in the Shanxi Rift, China. Although several studies have been conducted on the JCF, its coseismic slip history and seismogenic capacity are still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…They suggested that the rupture pattern along the Litang fault is a "rupture cycle model" and divided the Holocene events into 3 rupture In recent years, researchers have used micromorphology of bedrock fault surfaces to identify paleoearthquakes, because trenching methods are not applicable to bedrock. In this issue, Zou et al study the Jiaocheng fault in the Shanxi rift, dominated by extension [17]. Two bedrock fault surfaces are investigated in detail, at SXC and SLZ along the northern and central segments of the fault.…”
Section: Fault Slip Rates and Paleoseismologymentioning
confidence: 99%
“…They suggested that the rupture pattern along the Litang fault is a "rupture cycle model" and divided the Holocene events into 3 rupture In recent years, researchers have used micromorphology of bedrock fault surfaces to identify paleoearthquakes, because trenching methods are not applicable to bedrock. In this issue, Zou et al study the Jiaocheng fault in the Shanxi rift, dominated by extension [17]. Two bedrock fault surfaces are investigated in detail, at SXC and SLZ along the northern and central segments of the fault.…”
Section: Fault Slip Rates and Paleoseismologymentioning
confidence: 99%